Functionalized Aluminum Nitride for Improving Hydrolysis Resistances of Highly Thermally Conductive Polysiloxane Composites - He, Mukun; Zhang, Lei; Ruan, Kunpeng; Zhang, Junliang; Zhang, Haitian; Lv, Peng; Guo, Yongqiang; Shi, Xuetao; Guo, Hua; Kong, Jie; Gu, Junwei (Nano-Micro Letters, 2025)
A series of divinylphenyl-acryloyl chloride copolymers (PDVB-co-PACl) is synthesized via atom transfer radical polymerization employing tert-butyl acrylate and divinylbenzene as monomers. PDVB-co-PACl is utilized to graft on the surface of spherical aluminum nitride (AlN) to prepare functionalized AlN (AlN@PDVB-co-PACl). Polymethylhydrosiloxane (PMHS) is then used as the matrix to prepare thermally conductive AlN@PDVB-co-PACl/PMHS composites with AlN@PDVB-co-PACl as fillers through blending and curing. The grafting of PDVB-co-PACl synchronously enhances the hydrolysis resistance of AlN and its interfacial compatibility with PMHS matrix. When the molecular weight of PDVB-co-PACl is 5100 g mol−1 and the grafting density is 0.8 wt%, the composites containing 75 wt% of AlN@PDVB-co-PACl exhibit the optimal comprehensive performance. The thermal conductivity (λ) of the composite is 1.14 W m−1 K−1, which enhances by 20% and 420% compared to the λ of simply physically blended AlN/PMHS composite and pure PMHS, respectively. Meanwhile, AlN@PDVB-co-PACl/PMHS composites display remarkable hydrothermal aging resistance by retaining 99.1% of its λ after soaking in 90 °C deionized water for 80 h, whereas the λ of the blended AlN/PMHS composites decreases sharply to 93.7%. Highlights: 1 Copolymer of divinylphenyl-acryloyl chloride copolymers (PDVB-co-PACl) is designed and synthesized to graft on the surface of aluminum nitride (AlN) to improve its hydrolysis resistance. 2 AlN fillers functionalized by PDVB-co-PACl with the molecular weight of 5100 g mol-1 exhibits the highest hydrolysis resistance and the lowest interfacial thermal resistance. 3 When the mass fraction of AlN@PDVB-co-PACl is 75 wt% and the grafting density of PDVB-co-PACl is 0.8 wt%, the λ for AlN@PDVB-co-PACl/PMHS composites is 1.14 W m-1 K-1 and maintains 99.1% after soaking in 90 °C deionized water for 80 h.